The Finnish Education as an Individualized Service System with a Reference to Students with Special Educational Needs - Hautamäki Ja; Podolskiy A.I (Moscow State University of Psychology and Education, 2021)
The paper deals with some educational aspects of going to school in Finland concerning students with special educational needs/services. We proceed from empirical observation. Then, the general context is given to interpret the data and extend the observed added value of individualized educational support. The latter, in its turn, requires the identification of a special need and the existence of suitable educational options. These two pieces of information need to match optimally: early birds get the biggest harvest, and even if special education is never too late, the service needs become more challenging and the solutions - more expensive. The core of this complicated dual process is the decision making with more or less complete information of both the needs and the available palette of educational actions. The fundamental dilemma is to navigate between two poles: if a pupil is left out by such educational measures which could have helped him/her to become a full member of society and economy, we have a moral problem. If the economical-educational complex is not providing the best research-supported educational tools, we also have a pedagogical problem. However, it is not universally proved that full integration is the best way; neither is it proved that we need an entire set of segregated and specialized schools for several different kinds of special needs.